Очищення олій центрифугуванням - Повар, Ігор Юрійович; Комар, Артем Станіславович; Povar, Ihor; Komar, Artem (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто процес очищення рослинних олій центрифугуванням як один із найпоширеніших фізичних способів видалення механічних домішок із олії-сирцю. Показано, що ефективність центрифугування істотно перевищує гравітаційне відстоювання, оскільки в полі відцентрових сил осадження частинок відбувається значно інтенсивніше. Наведено фізичні передумови процесу, базові аналітичні залежності для опису сил, що діють на тверді частинки, а також узагальнено особливості роботи дискових, барабанних, вертикальних фільтрувальних і конічних центрифуг. Встановлено, що центрифугування є ефективним насамперед на стадії попереднього очищення олій від грубодисперсних механічних домішок, однак не забезпечує повного вилучення дрібнодисперсної зависі та первинних продуктів окиснення. Обґрунтовано доцільність поєднання центрифугування з фільтрацією або адсорбційним доочищенням для покращення якості готового продукту. /// EN: Unrefined vegetable oils after pressing or extraction contain mechanical impurities, shell particles, protein and mucous substances, phospholipids, free fatty acids, pigments and initial oxidation products, which impair the transparency, stability and shelf life of the product. Therefore, primary purification of oils is a mandatory stage of the technological process. The aim of the work is to generalize the theoretical and technological foundations of vegetable oil purification by centrifugation, analyze the efficiency of various centrifuge designs, and determine the limits of application of this method in the technology of primary oil purification. The article presents the results of an analysis of modern research, considers vegetable oil purification by centrifugation as one of the main physical methods for removing mechanical impurities from crude oil. It is shown that centrifugation is substantially more effective than gravitational settling because the separation of solid particles occurs under centrifugal acceleration. The physical basis of the process, the main analytical equations, and the design features of disc-stack, drum, vertical filtering, and conical centrifuges are summarized. It is established that centrifugation is highly effective at the stage of preliminary purification of oils from coarse suspended particles, but it does not ensure complete removal of finedispersed impurities and primary oxidation products. Therefore, for deeper purification, centrifugation should be combined with filtration or adsorption treatment. To enhance the purification process, centrifugation with filtration or adsorption purification is necessary. This approach corresponds to current trends in the technology of purification of vegetable oils and allows us to improve the stability, purity and conservation of the product.
Oil purification by centrifugation
Keywords: рослинна олія; центрифугування; очищення олії; механічні домішки; відцентрова сила; осадження; дискова центрифуга; конічний очищувач; фільтрація; адсорбція; vegetable oil; centrifugation; oil purification; mechanical impurities; centrifugal force; sedimentation; disc-stack centrifuge; conical purifier; filtration; adsorption